Characterizing dissolved inorganic and organic nutrients in the oligotrophic Kuroshio Current off eastern Taiwan during warm seasons - Hung, Jia-Jang; Tsai, Sheng-Hsian; Lin, Yen-Hui; Hsiang, Zhi-Ying (Frontiers in Marine Science, 2024)
This study conducted sensitive and precise analyses of dissolved organic nitrogen (DON) and dissolved organic phosphorus (DOP) concentrations and trace concentrations of nitrate and nitrite (N+N) and soluble reactive phosphorus (SRP) in seawater. The methods were applied to investigate the distributions and controls of N+N, SRP, DON, and DOP in the oligotrophic Kuroshio Current (KC) area off eastern Taiwan during warm seasons. The water in the studied area was classified into four major types: typical Kuroshio water (KW), KW influenced by the East China Sea water, KC influenced by the South China Sea (SCS) water, and KW influenced by the SCS water and river plumes, which is confined to the coastal zone. Nutrient distributions in KC revealed very low N+N (0.002-0.40 µM) and SRP (0.015-0.125 µM) concentrations but high DON (<8 µM) and DOP (<0.3 µM) concentrations above the nutricline depth, which accounted for >80% of TDN and TDP, respectively; theses concentrations can primarily be attributed to strong, permanent surface stratification. Among the water types, KW had the lowest N+N, SRP, DON, and DOP concentrations but greatest chlorophyll maximum depth and nutricline depth, except for in locations influenced by island-induced upwelling. The concentrations of all nutrients increased by various degrees in the other water types, which was attributed to the exchange and mixing of different water masses and coastal uplift of subsurface waters. KW was not only highly oligotrophic but also N+N-limited reflected from very low [N+N]/[SRP] ratio (0.02-0.15) in the mixed layer (ML). Overall, the N+N limitation and high nitrate anomaly value (N*: 2.47 ± 0.16 µM) above the nutricline depth strongly indicate prevailing N2 fixation at the surface of KW. Very high DON/DOP ratio in KW (16.9-69.1) probably resulted from the release of N-rich organic nutrients from phytoplankton including N2 fixers at the surface and faster recycling of DOP than DON in deep waters. Persistent coastal uplift of subsurface water occurs everywhere over the shore-side region of the KC, resulting in increasing surface concentrations of nutrients and chlorophyll a. Overall, the aforementioned physical and biogeochemical processes determined the upper-ocean distributions of nutrient species in warm seasons.